2014
DOI: 10.1186/s12983-014-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar phylogeography of the northern pike (Esox lucius) and its relationship to the Amur pike (E. reichertii)

Abstract: Background: Freshwater fishes of the genus Esox are found throughout the Holarctic region. The northern pike (E. lucius) has a circumpolar distribution whereas the assumed sister species the Amur pike (E. reichertii) is only found in the Amur region. The genetic structure and post-glacial dispersal of these species are not well known. Here, we use sequence variation at two mitochondrial DNA regions (cytb and D-loop) to investigate the phylogeography, infer location of glacial refugia and investigate the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 56 publications
9
45
3
Order By: Relevance
“…3) and is clearly referred to this species genetically, consistent with the morphological analyses. The D-loop sequence of the newly described specimen matches haplotype 'B' of Skog et al (2014) found across the Holarctic including a modern Alaskan sample and haplotype Eld7 (Maes et al, 2003) from Ontario, Canada. The Maes et al (2003) sequences were not included in the network analysis, as their inclusion led to too many sites with missing information.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…3) and is clearly referred to this species genetically, consistent with the morphological analyses. The D-loop sequence of the newly described specimen matches haplotype 'B' of Skog et al (2014) found across the Holarctic including a modern Alaskan sample and haplotype Eld7 (Maes et al, 2003) from Ontario, Canada. The Maes et al (2003) sequences were not included in the network analysis, as their inclusion led to too many sites with missing information.…”
Section: Resultsmentioning
confidence: 53%
“…In contrast, the timing and genetic affinity of the specimen documented here combined with documented distribution patterns of genetic diversity in modern populations of Northern pike (Skog et al, 2014;Lopez, unpublished data) suggest that Northern pike populations expanded rapidly following glacial retreat. There is no evidence reported to date that indicates the survival of Northern pike in Beringia through the habitat changes associated with Pleistocene glaciations.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations